5MF6255: excavations at an early archaic basin house site in the Yampa River Valley, Moffat County, Colorado - Slaughter, Stephanie, author; LaBelle, Jason, advisor; Zeidler, James, committee member; Fiege, Mark T., committee member (Colorado State University. Libraries, 2010)
Metcalf Archaeological Consultants, Inc., excavated site 5ME6255 in the late summer and early fall of 2006. The site had been discovered during the open trench inspection of Wyoming Interstate Company’s Piceance Basin Expansion Project pipeline. As observed in the trench, the site contained a dark cultural stain located about 1.6 m below bladed surface, which was identified as a possible basin house. Its stratigraphic position within a zone of heavy calcium carbonate deposits suggested an age of 7000 BP or greater, placing the site firmly within the Pioneer period of the Archaic era. Very few sites of this age have been excavated in northwestern Colorado, making 5MF6255 important for establishing basic information about this period of prehistory, regardless of whether or not it was a basin house. A total of 104 complete and partial 1 m by 1 m units were excavated in one large block to explore the contextual integrity of the feature, the nature of the stain, and search for any associated ancillary features. Results of excavation revealed the site consisted of three basin houses, one of which had two rooms, as well as 15 other pit features. A preliminary charcoal sample from the upper layers of the south end of the initially identified basin house was submitted for radiocarbon analysis and returned two intercept dates of 7935-8070 cal BP and 8084-8159 cal BP (2-sigma), dating the site to the early Pioneer Period of the Archaic Era. It is one of the oldest basin house known in the northern Colorado River basin area. Cultural material recovered from the site is described, and the research contributions resulting from these investigations are detailed, iii including its place in the chronology of northwestern Colorado, paleoenvironmental data obtained for the project as a whole is described, settlement and subsistence strategies are discussed, and finally, morphology of both the house features and pit features are detailed. A short comparison of this site to other Pioneer-era sites in the regions is also discussed, placing the site within the context of the larger early Archaic adaptive strategies of the region.
Covers not scanned.
Keywords: Excavations (Archaeology) -- Colorado -- Moffat County